Factors That Affect The Occurrence of Breast Cancer in Women of Childbearing Age in Muaratais II Village Batang Angkola District, South Tapanuli District in 2019 - Desi Meliana Gultom; Normayanti Rambe (Institute of Computer Science (IOCS), 2021)
Breast cancer is the most common type of cancer in women. The purpose of the study to find out the factors that affect the occurrence of breast cancer in women of childbearing age in Muaratais II Subdistrict Batang Angkola South Tapanuli District in 2019. Research time was conducted from April to May 2019. The sample was taken by 26 women of childbearing age. This type of research is analytical with cross-sectional methods. And analyze the data with the chi-square test. The results of the study of statistical tests of knowledge variables obtained a value of p= 0.007 (p< 0.05), and lifestyle variables obtained a value of p = 0.002 (p< 0.05) means there is a lifestyle influence on the occurrence of breast cancer. In conclusion, there is an influence of knowledge, and lifestyle on the occurrence of breast cancer. Advice for health workers to provide more information about the occurrence of breast cancer in women of childbearing age.